Nahdlatul Ulama’s Domination in Madura: An Eco-Anthropological Perspective - Vicky Izza El Rahma; Nasiri Nasiri (International Journal of Islamic Thought and Humanities, 2024)
On the basis of the ecological anthropology perspective, this study analyzes the complex relations between the environmental environment and the Muslim population in Madura so that traditionalism Islam dominates their religious culture in the Nahdlatul Ulama model. This study reveals that Islamization history in Madura, kiasi's social, religious role, and Syaichona Kholil’s figure became the three main lead factors that drive traditional religious culture in Madura, especially in Bangkalan. Two of the three factors mentioned earlier are closely related to the geographical location and ecological condition of Bangkalan.